Clinical characteristics and outcome of cancer diagnosed during pregnancy - Shim, Min Hee; Mok, Chi-Won; Chang, Kylie Hae-Jin; Sung, Ji-Hee; Choi, Suk-Joo; Oh, Soo-young; Roh, Cheong-Rae; Kim, Jong-Hwa (Obstetrics & gynecology science, 2016)
The aim of this study is to describe the clinical characteristics and outcome of cancer diagnosed during pregnancy. This is a retrospective cohort study of women who were diagnosed with cancer during pregnancy at a tertiary academic hospital between 1995 and 2013. Maternal characteristics, gestational age at diagnosis, and type, stage, symptoms and signs of cancer for each patient were retrieved from the medical records. The cancer treatment, pregnancy management and the subsequent perinatal and maternal outcomes for each cancer were assessed. A total of 87 women were diagnosed with cancer during pregnancy (172.6 cases per 100,000 deliveries). The most common cancer was breast cancer (n=20), followed by gastrointestinal (n=17), hematologic (n=13), thyroid (n=11), central nervous system (n=7), cervical (n=7), ovarian (n=5), lung (n=3), and other cancers (n=4). Eighteen (20.7%) patients terminated their pregnancies. In the 69 (79.3%) patients who maintained their pregnancies, one patient miscarried and 34 patients delivered preterm. Of the preterm babies, 24 (70.6%) were admitted to the neonatal intensive care unit and 3 (8.8%) of those expired. The maternal mortality rate was 31.0%, with highest rate seen with lung cancers (66.7%), followed by gastrointestinal (50.0%), central nervous system (50.0%), hematologic (30.8%), breast (25.0%), ovarian (20.0%) cervical (14.3%), and thyroid cancers (0%). The clinical characteristics and outcome of cancer during pregnancy were highly variable depending on the type of cancer. However, timely diagnosis and appropriate management of cancer during pregnancy may improve both maternal and neonatal outcome.